Exploring the GRB–Supernova Connection: Does a Superluminous Hypernova Population Exist? - Achille Fiore; Ludovica Crosato Menegazzi; Giulia Stratta (Galaxies)
Observations of several gamma-ray bursts (GRBs) that are temporally and spatially compatible with energetic supernovae (hypernovae) have established their common origin. In one case (GRB 111209A/SN 2011kl), the associated supernova was classified as superluminous (SN 2011kl). The exceptional duration of the observed gamma-ray prompt emission of GRB 111209A (about 7 h) is widely considered key to unlocking the physics behind the still mysterious origin of superluminous supernovae (SLSNe). We review the main observational and theoretical findings that may link some ultra-long GRBs to SLSNe. Specifically, we examine notable events and the role of progenitors and host galaxies in shaping these phenomena and focus on the proposed models. While a magnetar central engine is a plausible mechanism for both luminous and long-duration GRBs, a conclusive answer remains elusive, as alternative explanations are still viable. Further observational and theoretical work is required to clarify progenitor pathways and explosion mechanisms, potentially extending the classical GRB-SN connection to rare superluminous hypernovae.